Case report: Injected corticosteroids for treating leprosy isolated neuritis - Clarissa Neves Spitz; Clarissa Neves Spitz; Clarissa Neves Spitz; Izabela Jardim Rodrigues Pitta; Izabela Jardim Rodrigues Pitta; Ligia Rocha Andrade; Ligia Rocha Andrade; Ligia Rocha Andrade; Anna Maria Sales; Euzenir Nunes Sarno; Nivaldo Ribeiro Villela; Roberta Olmo Pinheiro; et al. (Frontiers in Medicine, 2023)
One of the main manifestations of leprosy is peripheral nerve impairment. Early diagnosis and treatment are important to reduce the impact of neurological impairment, which can cause deformities and physical disabilities. Leprosy neuropathy can be acute or chronic, and neural involvement can occur before, during, or after multidrug therapy, and especially during reactional episodes when neuritis occurs. Neuritis causes loss of function in the nerves and can be irreversible if left untreated. The recommended treatment is corticosteroids, usually through an oral regimen at an immunosuppressive dose. However, patients with clinical conditions that restrict corticosteroid use or that have focal neural involvement may benefit from the use of ultrasound-guided perineural injectable corticosteroids. In this study, we report two cases that demonstrate how the treatment and follow-up of patients with neuritis secondary to leprosy, using new techniques, can be provided in a more individualized way. Nerve conduction studies in association with neuromuscular ultrasound were used to monitor the response to treatment with injected steroids, focusing on neural inflammation. This study provides new perspectives and options for this profile of patients.